The effects of Cernitin® on inflammatory parameters and benign prostatic hyperplasia: An in vitro study. (25th July 2019) - Dizeyi, Nishtman; Mattisson, Ingrid Yao; Ramnemark, Lena; Grabe, Magnus; Abrahamsson, Per‐Anders
Abstract : The pollen extract Cernitin® is widely used for treatment of benign prostatic hyperplasia (BPH) and non‐bacterial chronin prostatitis. However, little is known about the underlying molecular mechanisms to explain the clinical effects of Cernitin®. In this study, we sought to investigate the cellular mechanisms by which Cernitin® induces its effects on human prostatic cell lines BPH‐1 and WPMY‐1 and primary human peripheral blood mononuclear cells (hPBMCs) in vitro. We examined the effects of Cernitin® formulas T60 and GBX on the protein expression, proliferation, and cytokines production. Results revealed that Cernitin® upregulated antiinflammatory cytokine interleukin (IL)‐10 and its receptors IL‐10RA and IL‐10B in addition to the upregulation of tumour necrosis factor‐related apoptosis‐inducing ligand in hPBMC. Interestingly, the levels of proinflammatory cytokines IL‐6 and IL‐8 were also increased. Furthermore, Cernitin® had significantly increased the level of IL‐10 in BPH‐1 and WPMY‐1 cells. The level of IL‐6 was also significantly increased in these cells although both T60 and GBX inhibited STAT‐3 phosphorylation. Moreover, Cernitin® formulas had significantly reduced androgen receptor and prostate‐specific antigen protein expression in stromal cells ( p  < .05). Treatment with GBX and T60 had significantly inhibited proliferation of BPH ( p  < .001) and stromal cells ( p  < .05), in a dose‐dependent manner. Taken together, treatment with Cernitin® showed to regulate cytokines level in both prostatic cell lines and hPBMCs and it was associated with decreased androgen receptor and prostate‐specific antigen levels WPMY‐1 cells.